Toxicity of cadmium on some tropical aquatic species including lates calcarifer - M. Shazili, Noor A.
The acute toxicity of cadmium was investigated on some commercially important cultured species of fish in Malaysia. The organism studied were the grass carp Ctenopharyngodon idella and the barb Puntius gonionotus which are freshwater species;the sea bass,Lates calcifarer, a marine species and the Malaysian giant prawn,Microbrachium rossenbergii which is a freshwater species with early life stages requiring brackishwater. M.rosenbergii was the most sensitive to cadmium with a 96 h LC 50 value of 0.038mg Cd/L. C.idella and p.gonionotus had 96 h LC 50 values of 0.96 and 1.25mg Cd/L respectively. Lates calcarifer while highly tolerant to cadmium in 15 and 30 ppt salinity (96 h LC 50 of 15 and 19.5mg Cd/Lrespectively) was found to be more sensitive than the two freshwater fish species studied at 5 ppt salinity (96 hLC 50 of 0.74mg Cd/L).